The Influence of the Learning Environment on Islamic Religious Education Learning Outcomes at SMP Puja Handayani Palembang - Saputra, Novrian Eka; Muhammad Albab Mananna; Hartatiana; Muhammad Win Afgani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The low learning outcomes in Islamic Religious Education (IRE) at SMP Puja Handayani Palembang prompted an investigation into learning environment factors. This study aims to analyze the comprehensive effects of the physical, social, and psychological learning environment on the IRE learning outcomes of eighth-grade students. Employing a quantitative approach with a correlational survey method, the population consisted of 120 students, with a sample of 40 students selected through simple random sampling. Data were collected using validated Likert-scale questionnaires (α = 0.879 for variable X; α = 0.820 for variable Y) and official IRE scores, and were analyzed using normality testing (Kolmogorov–Smirnov Sig. = 0.200), linearity testing (Sig. = 0.515), and simple linear regression in SPSS 25. The results indicate a significant positive effect of the learning environment on IRE learning outcomes (t = 2.325; Sig. = 0.026 < 0.05). In conclusion, a conducive learning environment substantially enhances IRE academic achievement and the formation of students’ religious character, underscoring the need to optimize infrastructure and foster a positive classroom climate.